Tuition fees - Linking Student Financial Participation to Universities Budgets - Chaveiro Vitorino, Duarte Filipe (2024)
This study explores into the intricate relationship between student financial contributions and the economic context of universities. This study explores the correlation between student financial participation and the economic landscape of the countries where these universities operate. By analysing funding amounts, university budgets, and institutional wealth, this research uncovers crucial correlations that illuminate the financial dynamics within universities. Through a combination of qualitative examination and quantitative analysis, this thesis aims to identify similarities in financial characteristics across universities in different countries. The study provides a detailed and nuanced analysis of the financial landscapes of these institutions, offering valuable insights into the complex interplay between student financial involvement and the overall economic context of universities.